Effects of massage on newborn infants with jaundice: A meta-analysis - Mengjie Lei; Tingting Liu; Yufeng Li; Yaqian Liu; Lina Meng; Changde Jin (Elsevier, 2018)
Objective: This meta-analysis aims to systematically evaluate the effects of massage on infants with jaundice. Methods: Multiple electronic databases, including Cochrane Library, PubMed, EMBASE, Web of Science, China Biology Medicine (CBM), Wan Fang Data, VIP Database for Chinese Technical Periodicals and China National Knowledge Infrastructure (CNKI), were used to search for studies on the effects of massage on infants with jaundice. Data were analysed by Rev Man 5.3. Results: A total of 14 randomised controlled trials with 1889 patients were included. Statistically significant difference in percutaneous bilirubin [MD = −1.21, 95% CI (−1.90, −0.52), P < 0.05; MD = −2.00, 95% CI (−2.68, −1.32), P < 0.05; MD = −2.00, 95% CI (2.56, −1.44), P < 0.05; MD = −1.93, 95% CI (−2.44, −1.43), P < 0.05] was found between two groups at 48, 72, 96 and 168 h. Studies on the serum total bilirubin level were divided into two subgroups according to sample size, and the results of subgroup analysis showed that the serum total bilirubin level in the intervention group was significantly lower than that in the control group [MD = −52.06, 95% CI (−57.76, −46.36), P < 0.05 and MD = −10.65, 95% CI (−14.66, −6.63), P < 0.05]. Statistically significant difference in defecation frequency was observed between the two groups at 48 h after birth[SMD = 0.44, 95%CI (0.02, 0.87), P < 0.05]. Conclusion: Massage can decrease serum total bilirubin and percutaneous bilirubin levels and increasing defecation frequency. However, due to heterogeneity among studies, numerous multi-centre, large-sample and high-quality randomised controlled trials are needed to verify the effects of massage. Keywords: Jaundice, Massage, Meta-analysis, Neonate